2015
DOI: 10.3109/00365521.2015.1054424
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between long-term outcome and steroid therapy in type 1 autoimmune pancreatitis: relapse, malignancy and side effect of steroid

Abstract: CST reduces relapse of AIP. However, CST causes serious side effects, particularly in relapsing patients. Alternative maintenance therapy to prevent relapse is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…To our knowledge, this is the first randomised controlled trial of corticosteroid therapy in patients with AIP. Although it was suggested by retrospective studies,8 9 16 21 our results showed that maintenance therapy until 3 years might be useful for the prevention of relapses in patients with AIP.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…To our knowledge, this is the first randomised controlled trial of corticosteroid therapy in patients with AIP. Although it was suggested by retrospective studies,8 9 16 21 our results showed that maintenance therapy until 3 years might be useful for the prevention of relapses in patients with AIP.…”
Section: Discussioncontrasting
confidence: 53%
“…The cumulative amount of PSL administered during the 3-year maintenance therapy at 5 mg/day of PSL is well below the cut-off value of 8694 mg/dL. The cumulative amount of PSL >10 000 mg, which corresponds approximately to a 5-year maintenance therapy,21 was a significant risk factor for the development of serious side effects. Importantly, the cumulative amounts of corticosteroid are increased in patients with relapses, because the relapsed cases are treated with readministration or dose up of PSL.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations